An analysis of over-the-counter and centralized stock lending markets - Huszár, Zsuzsa R. (2022)
We provide new insights about centralized and OTC stock lending in the context of Tokyo Stock Exchange listed stocks from July 2006 to December 2009. We find that not only the demand drivers in the two markets are significantly different but also the pricing efficiency implications of the alternative markets are different. Specifically, we find that higher OTC stock lending activity is associated with greater pricing efficiency and better liquidity. The benefits of the centralized market on average is less clear, but when the OTC market is constrained, it is shown to relax short-sale constraints and improve liquidity.